A two-stage process facilitating microbial lipid production from N-acetylglucosamine by Cryptococcus curvatus cultured under non-sterile conditions. (June 2018) - Tang, Mou; Zhou, Wenting; Liu, Yi; Yan, Jiabao; Gong, Zhiwei
Graphical abstract: Highlights: A two-stage process using nitrogen-rich GlcNAc was described for lipid production. The inoculum age and inoculation size significantly influenced lipid production. The process rendered superior lipid production under non-sterile conditions. Lipid content and lipid yield reached as high as 56.9% and 0.23 g/g, respectively. Acetate released from GlcNAc could be completely consumed by C. curvatus . Abstract: N -acetylglucosamine (GlcNAc), the monomeric constituent of chitin, is rarely studied for lipid production by oleaginous species. This study demonstrated that Cryptococcus curvatus had a great capacity to convert GlcNAc into lipid with high yield using a two-stage production process. Optimal inoculum age and inoculation size strongly improved the two-stage lipid production efficiency. More interestingly, this process rendered superior lipid production under non-sterile condition. The acetate liberated from GlcNAc was consumed timely, while the NH4 + released was rarely assimilated. Lipid titre, lipid content and lipid yield reached 9.9 g/L, 56.9% and 0.23 g/g, respectively, which were significantly higher than those from the conventional process where cell growth and lipid accumulation were coupled. The resulting lipid samples had similar fatty acid compositional profiles to those of vegetable oil, suggesting their potential for biodiesel production. These findings strongly supported the two-stage process as an attractive strategy for better techno-economics of the chitin-to-biodiesel routes.